Studies on bacterial cellulose produced by a novel strain of Lactobacillus genus. (1st February 2020) - Khan, Hina; Kadam, Ashish; Dutt, Dharm
Graphical abstract: Highlights: Lactobacillus hilgardii is herein shown to be a novel bacterium capable of producing BC. The composition of BC was analyzed by acid hydrolysis followed by pre-column derivatization HPLC. The BC film was characterized by ATR-FTIR, XRD, FE-SEM, TEM, 13 C CP/ MAS NMR, and TG/DTG. The new strain showed the high productivity of BC in fructose-containing Y medium. Abstract: The present study aimed to explore a novel attribute of the bacterium Lactobacillus hilgardii IITRKH159, isolated from Sapodilla, which was found to produce Bacterial cellulose. The compositional analysis of BC was carried out by HPLC system using pre-column derivatization with 1-phenyl-3-methyl-5-pyrazolone showed that it consisted of glucan. The Physiochemical study of BC showed that it had bacterial nano-cellulose like structure, immensely pure, highly crystalline (90.25%) and significantly enriched with Iα form of cellulose. Additionally, FE-SEM and TEM of the BC revealed the morphological similarities with bacterial nano-cellulose due to the presence of a reticulated structure consisting of nano-sized fibrils with an average width of 45 nm. The effect of different carbon sources was analyzed to evaluate BC production and demonstrated the production of 7.23 ± 0.59 g L −1 BC with conversions yield (0.30 g BC/g sugar) and productivity (0.45 ± 0.15 g L −1  d −1 ) in a modified Y-medium after 16 days of cultivation.